2013
DOI: 10.1021/cn400039s
|View full text |Cite
|
Sign up to set email alerts
|

Retinoic Acid-Elicited RARα/RXRα Signaling Attenuates Aβ Production by Directly Inhibiting γ-Secretase-Mediated Cleavage of Amyloid Precursor Protein

Abstract: Retinoic acid (RA)-elicited signaling has been shown to play critical roles in development, organogenesis, and the immune response. RA regulates expression of Alzheimer's disease (AD)-related genes and attenuates amyloid pathology in a transgenic mouse model. In this study, we investigated whether RA can suppress the production of amyloid-β (Aβ) through direct inhibition of γ-secretase activity. We report that RA treatment of cells results in significant inhibition of γ-secretase-mediated processing of the amy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
18
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(18 citation statements)
references
References 41 publications
0
18
0
Order By: Relevance
“…However, we suggest here that ADAM10 is implicated in RA neuroprotection against Aβ-induced DSBs, especially as the Presenilin-1 protein, corresponding in our experiments to the immature uncleaved form [42], and the BACE1 protein did not show an increase in expression. Furthermore, it was already shown that RA inhibits the γ-secretase, thus increasing APP [34]. Note that the increase of the 110 kDa APP signal suggests that, despite increased cleavage at the α-site, there is an enhanced APP expression due to the activated RAdependent metabolism.…”
Section: Retinoic Acid Decreases the Amyloid Cascade In Youngmentioning
confidence: 83%
See 1 more Smart Citation
“…However, we suggest here that ADAM10 is implicated in RA neuroprotection against Aβ-induced DSBs, especially as the Presenilin-1 protein, corresponding in our experiments to the immature uncleaved form [42], and the BACE1 protein did not show an increase in expression. Furthermore, it was already shown that RA inhibits the γ-secretase, thus increasing APP [34]. Note that the increase of the 110 kDa APP signal suggests that, despite increased cleavage at the α-site, there is an enhanced APP expression due to the activated RAdependent metabolism.…”
Section: Retinoic Acid Decreases the Amyloid Cascade In Youngmentioning
confidence: 83%
“…Indeed, RA can increase, via the RARα receptor, the expression of ADAM10 (a disintegrin and metalloproteinase domain-containing protein 10), the major α-secretase [32], more than it increases the β-site cleaving enzyme BACE1, a β-secretase [33]. Furthermore, RA achieves a similar result by inhibiting the γ-secretase (or Presenilin-1) activity through activation of the Extracellular Signal-Regulated Kinase (ERK) 1/2 [34]. Thus, by changing the expression of enzymes of the amyloid cascade, RA might also prevent the formation of Aβ-induced DSBs and be a factor of neuroprotection against Aβ-induced DSBs and not just of DSB repair.…”
Section: Introductionmentioning
confidence: 99%
“…This effect is mediated by RA-responsive elements upstream of the ADAM10 coding region [ 30 , 31 ]. RA can also inhibit the γ -secretase activity through activation of the Extracellular Signal Regulated Kinase, ERK1/2 [ 32 ]. Secondly, vitamin A and its derivatives appear to inhibit A β oligomerisation in vitro , A β deposition, and tau phosphorylation in AD mouse models [ 33 ].…”
Section: Introductionmentioning
confidence: 99%
“…More precisely, only retinoic acid ␣ agonists (e.g., AM-580, Roche) reduced the number of A␤ plaques, whereas retinoic acid ␤ (e.g., CD-2019) or retinoic acid ␥ agonists (e.g., CD-437) had no effect on plaque load [420,421]. The A␤ production is attenuated by direct inhibition of ␥secretase-mediated cleavage of A␤PP [422]. Retinoic acid-elicited RAR␣/RXR␣ signaling attenuated the A␤ production by direct inhibition of ␥-secretasemediated cleavage of A␤PP [423].…”
Section: Retinoid X Receptorsmentioning
confidence: 98%
“…The A␤ production is attenuated by direct inhibition of ␥secretase-mediated cleavage of A␤PP [422]. Retinoic acid-elicited RAR␣/RXR␣ signaling attenuated the A␤ production by direct inhibition of ␥-secretasemediated cleavage of A␤PP [423]. The retinoic acid-inducible gene-I (RIG-1) receptor is significantly elevated in the temporal cortex and plasma in patients with MCI [424].…”
Section: Retinoid X Receptorsmentioning
confidence: 99%